Validity and reliability of self-reported weight and height measures for the diagnoses of adolescent's nutritional status - Enes, Carla Cristina; Fernandez, Priscila Maria Fúncia; Voci, Silvia Maria; Toral, Natacha; Romero, Alexandre; Slater, Betzabeth (Revista brasileira de epidemiologia, 2009)
PURPOSE: To assess the validity and reliability of self-reported height, weight, and Body Mass Index (BMI) to diagnose the nutritional status of adolescents. METHODS: The study included 360 public school students of both genders, with ages ranging from 10 to 15 years. Adolescents self-reported their weight and height, and these values were later obtained directly by interviewers. The validity of BMI based on self-reported measures was calculated using sensitivity and specificity indexes, and positive predictive value (PPV). Agreement between self-reported and measured BMI was evaluated using Kappa's weight coefficient, the Lin correlation coefficient, and Bland-Altman and Lin's plots. RESULTS: Both girls and boys underestimated their weight (-1.0 girls and boys) and height (girls - 1.2 and boys - 0.8) (p < 0.001). BMI presented moderate agreement between measured and self-reported values. Sensitivity of estimated BMI based on reported measures to classify obese subjects was higher for boys (87.5%) than it was for girls (60.9%), whereas specificity was higher for girls (92.7%) than it was for boys (80.6%). PPV was high only for classification of normal-weight adolescents. CONCLUSIONS: Self-reported measures of weight and height in adolescents do not present valid measures; therefore, they should not be used to replace measured values. Additionally, we observed that 10% of obese boys and 40% of obese girls could have remained unidentified if we had used only self-reported measures, emphasizing the effects of the low reliability of self-reporting. OBJETIVO: Avaliar a validade do peso, estatura e Índice de Massa Corporal (IMC) referidos e sua confiabilidade para o diagnóstico do estado nutricional de adolescentes de Piracicaba. MÉTODOS: Participaram do estudo 360 adolescentes de ambos os sexos, de escolas públicas de Piracicaba, com idade entre 10 e 15 anos. Os adolescentes auto-relataram seu peso e estatura, sendo esses valores obtidos por medidas diretas, logo em seguida, pelos entrevistadores. A validade do IMC referido foi calculada segundo índices de sensibilidade, especificidade e valor preditivo positivo (VPP). Avaliou-se a concordância entre as categorias de IMC obtido por meio das medidas referidas e aferidas a partir do coeficiente kappa ponderado, coeficiente de correlação de Lin. e gráficos de Bland e Altman e Lin. RESULTADOS: Verificou-se que tanto os meninos quanto as meninas subestimaram o peso (-1,0 meninas e meninos) e a estatura (meninas -1,2 e meninos -0,8) (p < 0,001). Os valores de IMC aferidos e referidos apresentaram uma concordância moderada. A sensibilidade do IMC referido para classificar os indivíduos obesos foi maior para os meninos (87,5%), enquanto a especificidade foi maior para as meninas (92,7%). O VPP foi elevado somente para a classificação da eutrofia. CONCLUSÕES: As medidas referidas de peso e estatura de adolescentes não representam medidas válidas e, portanto, não devem ser usadas em substituição aos valores mensurados. Além disso, verificou-se que 10% dos meninos obesos e 40% das meninas obesas poderiam permanecer não identificados utilizando-se as medidas auto-referidas, confirmando a baixa validade das medidas auto-referidas.